Neuronal cell type specific roles for Nprl2 in neurodevelopmental disorder-relevant behaviors - Brianne Dentel; Lidiette Angeles-Perez; Abigail Y. Flores; Katherine Lei; Chongyu Ren; Andrea Pineda Sanchez; Peter T. Tsai (Neurobiology of Disease)
Loss of function in the subunits of the GTPase-activating protein (GAP) activity toward Rags-1 (GATOR1) complex, an amino-acid sensitive negative regulator of the mechanistic target of rapamycin complex 1 (mTORC1), is implicated in both genetic familial epilepsies and Neurodevelopmental Disorders (NDDs) (Baldassari et al., 2018). Previous studies have found seizure phenotypes and increased activity resulting from conditional deletion of GATOR1 function from forebrain excitatory neurons (Yuskaitis et al., 2018; Dentel et al., 2022); however, studies focused on understanding mechanisms contributing to NDD-relevant behaviors are lacking, especially studies understanding the contributions of GATOR1's critical GAP catalytic subunit, nitrogen permease regulator like-2 (Nprl2). Given the clinical phenotypes observed in patients with Nprl2 mutations, in this study, we sought to investigate the neuronal cell type contributions of Nprl2 to NDD behaviors. We conditionally deleted Nprl2 broadly in most neurons (Synapsin1cre), in inhibitory neurons only (Vgatcre), and in Purkinje cells within the cerebellum (L7cre). Broad neuronal deletion of Nprl2 resulted in seizures, social and learning deficits, and hyperactivity. In contrast, deleting Nprl2 from inhibitory neurons led to increased motor learning, hyperactive behavior, in addition to social and learning deficits. Lastly, Purkinje cell (PC) loss of Nprl2 also led to learning and social deficits but did not affect locomotor activity. These phenotypes enhance understanding of the spectrum of disease found in human populations with GATOR1 loss of function and highlight the significance of distinct cellular populations to NDD-related behaviors. Significance statement: We aim to elucidate the neuronal-specific contributions of nitrogen permease regulator like-2 (Nprl2) to its neurodevelopmental disorder (NDD)-relevant phenotypes. We conditionally deleted Nprl2 broadly in neurons (Syn1cre), in inhibitory neurons (Vgatcre), and in cerebellar Purkinje cells (L7cre). We identify seizures only in the Syn1cre conditional mutant (cKO); hyperactivity, learning difficulties, social deficits, and impulsivity in the Syn1cre and Vgatcre cKOs; and social deficits, and fear learning deficits in L7cre cKOs. To our knowledge, we are the first to describe the behavioral contributions of Nprl2's function across multiple cell types. Our findings highlight both critical roles for Nprl2 in learning and behavior and also distinct contributions of select neuronal populations to these NDD-relevant behaviors.